2021
DOI: 10.1097/ccm.0000000000004968
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Electronic Signature of Infection in Electronic Health Record Data

Abstract: OBJECTIVES: Recent sepsis studies have defined patients as “infected” using a combination of culture and antibiotic orders rather than billing data. However, the accuracy of these definitions is unclear. We aimed to compare the accuracy of different established criteria for identifying infected patients using detailed chart review. DESIGN: Retrospective observational study. SETTING: Six hospitals from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Since the definition of sepsis requires laboratory data, including blood levels of creatinine and bilirubin and platelet counts, our extraction approach using diagnosis coding and treatment data on organ supports may underestimate the incidence compared to a more stringent extraction approach using laboratory data according to Sepsis-3. On the other hand, a recent report [ 37 ] found that the Rhee criteria [ 3 ] using a combination of culture and antibiotic orders approach is significantly less sensitive but more specific compared approaches to defining suspected infection via EHR data. We would expect the current study using suspected infection definition to be relatively specific and identify a more severely ill population.…”
Section: Discussionmentioning
confidence: 99%
“…Since the definition of sepsis requires laboratory data, including blood levels of creatinine and bilirubin and platelet counts, our extraction approach using diagnosis coding and treatment data on organ supports may underestimate the incidence compared to a more stringent extraction approach using laboratory data according to Sepsis-3. On the other hand, a recent report [ 37 ] found that the Rhee criteria [ 3 ] using a combination of culture and antibiotic orders approach is significantly less sensitive but more specific compared approaches to defining suspected infection via EHR data. We would expect the current study using suspected infection definition to be relatively specific and identify a more severely ill population.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis was identified by ICD-9/ICD-10 codes, which are known to be inaccurate. 37,38 However, the familiarity and generalizability of these codes offer an advantage over automated evaluation of clinical criteria, which has also been found to be inconsistent. 39 Additionally, in identifying the study's population, inclu-…”
Section: Discussionmentioning
confidence: 99%
“…There are advantages and disadvantages of both means of deriving study populations. EMR-based cohorts typically offer larger study populations but may have less granular data as well as decreased certainty in the diagnosis, whereas trial populations commonly have fewer subjects but certainty of sepsis or septic shock diagnosis and often highly regimented data ( 21 ).…”
Section: Discussionmentioning
confidence: 99%